Kluver-Bucy Syndrome after Meningoencephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Medical College of Georgia, Augusta, GA, report a 10-year-old girl with a history of Listeria monocytogenes meningoencephalitis, contracted at 2½ years of age, who developed behavioral changes consistent with Kluver-Bucy syndrome at 2 months following discharge.